Rito y desformance en la subalternización del ágora sodomizante - Fernandez Melchor, Álvaro Eduardo (2024)
This text offers an autoethnographic analysis of the performative action Polvo de Caballo, carried out in 2023 by Antonio Palacios and local artists during the 5th International Performance Encounter “No Lo Haga Usted Mismo”, in Aguascalientes, Mexico. The performance, executed in Plaza Jesús F. Contreras in the Historic Center, presents a critical reinterpretation of the surrounding public monuments. Additionally, the concept of desformance as a ritual is explored through a hermeneutic interpretation, encompassing the conceptual characters of Deleuze and Guattari in What is Philosophy? and confronting them with Latin American performances that subvert, modify, or destroy historical and popular icons from the region. The analysis focuses on Polvo de Caballo to establish a dialogue between the theory and practice of performance, understanding the action as a dialectical space between both. This interaction generates a "performativity of writing," extending the lived experience of the performative act into a theoretical and reflective realm, thus amplifying its impact. In this way, the performance is not only contained within its execution but is also projected into a written domain, enhancing its relevance beyond the initial performative moment.